Community Interest and the Future of Community Academy: a Case for Establishing a State Polytechnic in West-South Aceh - Febri Nurrahmi; Tanzir Masykar; Hery Wiharja; Andi Mustari; Haimi Ardiansyah; Mahlil Mahlil (Universitas Ahmad Dahlan, 2026)
This study examines community perceptions and levels of interest in the establishment of a state polytechnic in the West-South Aceh region, particularly following the collaborative initiative of D4 programs by Akademi Komunitas Negeri Aceh Barat (AKN Aceh Barat) and Politeknik Negeri Lhokseumawe (PNL). Using a quantitative cross-sectional design, data were collected through an online survey completed by 242 respondents. Descriptive statistics, t-tests, and one-way ANOVA were applied to assess perceptions across three key indicators: the urgency of establishing a polytechnic, personal interest in attending, and family interest in polytechnic education. Results indicate overwhelming support across demographic groups, with over 93% consider the establishment urgent, and more than 84% expressed personal or familial interest. Although men showed significantly higher personal interest than women, no significant differences were observed by region or education level. Community preferences for mining, maritime, and informatics programs demonstrate a clear connection to the region’s workforce demands and industrial profile. These findings provide strong empirical support for upgrading AKN Aceh Barat into a state polytechnic, addressing both educational and regional workforce development needs.